Markov switching in disaggregate unemployment rates - Marcelle Chauvet; Chinhui Juhn; Simon Potter (Federal Reserve Bank of New York, 2001)
We develop a dynamic factor model with Markov switching to examine secular and business cycle fluctuations in U.S. unemployment rates. We extract the common dynamics among unemployment rates disaggregated for seven age groups. The framework allows analysis of the contribution of demographic factors to secular changes in unemployment rates. In addition, it allows examination of the separate contribution of changes due to asymmetric business cycle fluctuations. We find strong evidence in favor of the common factor and of the switching between high and low unemployment rate regimes. We also find that demographic adjustments can account for a great deal of the secular change in the unemployment rate, particularly the abrupt increase in the 1970s and 1980s and the subsequent decrease.
Keywords: 330; Markov Switching; Unemployment; Common Factor; Asymmetries; Business Cycle; Baby Boom; Bayesian Methods; Arbeitslosigkeit; Konjunktur; Markovscher Prozess; Faktorenanalyse; Schätzung; USA